2007
DOI: 10.1007/978-0-387-72124-8_30
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Three Yersinia pestis CRISPR Loci Provides New Tools for Phylogenetic Studies and Possibly for the Investigation of Ancient DNA

Abstract: The precise nature of the pathogen having caused early plague pandemics is uncertain. Although Yersinia pestis is a likely candidate for all three plague pandemics, the very rare direct evidence that can be deduced from ancient DNA (aDNA) analysis is controversial. Moreover, which of the three biovars, Antiqua, Medievalis or Orientalis, was associated with these pandemics is still debated. There is a need for phylogenetic analysis performed on Y. pestis strains isolated from countries from which plague probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 20 publications
0
32
0
3
Order By: Relevance
“…CRISPR/Cas systems are described as a prokaryotic immune system against extrachromosomal elements, such as plasmids or viruses. This function requires a significant sequence similarity of the CRISPR spacers with these genetic elements (7,15,56,76). Hence, all T. tenax CRISPR spacers were checked for similarity against the genome sequences of 42 viruses known to infect archaeal organisms (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR/Cas systems are described as a prokaryotic immune system against extrachromosomal elements, such as plasmids or viruses. This function requires a significant sequence similarity of the CRISPR spacers with these genetic elements (7,15,56,76). Hence, all T. tenax CRISPR spacers were checked for similarity against the genome sequences of 42 viruses known to infect archaeal organisms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…46% of the bacterial genomes and in 84% of all Archaea, but not in viruses or eukaryotic genome sequences (23,24). Similarity searches of CRISPR spacers showed that some sequences match viruses and other extrachromosomal elements, such as plasmids, but rarely also chromosomal DNA (7,15,56,76). CRISPR loci are transcribed and processed into a series of smaller CRISPR RNAs (crRNAs), corresponding to spacer units with termini processed within the repeat region (29,45,72,73).…”
mentioning
confidence: 99%
“…As described above for the type II CRISPR-Cas system, the type I CRISPR-Cas system was found to be useful for typing of Yersinia pestis (type I-F) and Salmonella (types I-E and I-F) strains (35,36). In Y. pestis, CRISPR typing was able to identify the origin of the ancestor strains that caused the black plague (36).…”
Section: Figmentioning
confidence: 96%
“…In Y. pestis, CRISPR typing was able to identify the origin of the ancestor strains that caused the black plague (36). Whereas it had been assumed that the black plague originated from Mongolia, CRISPR typing suggested that this region harbored a different, less virulent Yersinia species (Yersinia microtus clade) (37).…”
Section: Figmentioning
confidence: 99%
“…Spoligotyping is based on differences between CRISPR-Cas systems to identify bacterial strains (315). This technique helps investigations of evolution and geographical and/or historical studies (316,317) and permits the identification of microbial populations (318) or the analysis of pathogen outbreaks (319). New spacer repeat units are inserted in 5= extremities of CRISPR arrays, which provide information on recent infections.…”
Section: Genetic Elements Controlling the Stability Of Mobile Elementsmentioning
confidence: 99%